DOI: 10.22215/etd/2018-12633
|View full text |Cite
|
Sign up to set email alerts
|

On Properties of Relatively Hyperbolic Groups

Abstract: We discuss a number of problems in relatively hyperbolic groups. We show that the word problem and the conjugacy (search) problem are solvable in linear and quadratic time, respectively, for a relatively hyperbolic group, whenever the corresponding problem is solvable in linear and quadratic time in each parabolic subgroup. We also consider the class R of finitely generated toral relatively hyperbolic groups. We show that groups from R are commutative transitive and generalize a theorem proved by Baumslag in [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Remark Theorem 1.3 leaves open the question if the above conditions are equivalent to ρ$\rho$ is being prefixsans-serifPk$\operatorname{\mathsf {P}}_k$‐Anosov relative to any weak cusp space. Using a different flow space (which is equivalent to ours when X$X$ is CATfalse(1false)${\rm CAT}(-1)$), Wang showed that this is the case [40]. …”
Section: Introductionmentioning
confidence: 99%
“…Remark Theorem 1.3 leaves open the question if the above conditions are equivalent to ρ$\rho$ is being prefixsans-serifPk$\operatorname{\mathsf {P}}_k$‐Anosov relative to any weak cusp space. Using a different flow space (which is equivalent to ours when X$X$ is CATfalse(1false)${\rm CAT}(-1)$), Wang showed that this is the case [40]. …”
Section: Introductionmentioning
confidence: 99%